(3GdebJVHs - (3CHhHcQ YHO GdbGgQ YHO GdQMef GdLQLGfjs; (3GdMSf Hf CMeO Hf YHO GdZaGQ GdaGQSj, CHh Ydj,J (B377 (3g` s ((3CHi SYjO YHOGdQMef Hf YHOGdUeO s)
(3ChdgG (B:s
(3jHJOF gPG GdeLdO HYO cdGe bdjd HHGH Mce GdSGcfjf EPG GdJbjfG s
(3BNQgG (B:s
(3jfJgi bHd HGH GdCaYGd GdKdGKjI GdeRjO ajgG s
(3Vef eLehY , JQJjHgG (B: (3GdKGfis
(3GdfSNI eYGQVI ai eJfgG Ydi NW GdaGQSi hai TQMgG Ydi NW GdLQLGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs